The underlying concept of Persian miniature paintings: Persian miniature paintings between 14th to 17th centuries / Mohammad Tirani - Tirani, Mohammad (2017)
Since Nineteen century until now many fine artists and art historians from western countries and also Muslim scholars tried to reveal the underlying techniques and content behind the Persian Miniature Paintings. Most of the early outcome of Western analysis and research works emphasized on decorative concept of miniature paintings until past decades that some Western and Persian-Muslim scholars like Henry Corbin, Oleg Grabar, Robert Hillenbrand, SH NASR, M. M. Ashrafi and many others started new argument about philosophical-mystical concept behind the miniature works. To unlock the mysteries of creating miniature works researchers referred- to mystical philosophy of Iran in that period. After that the great Sufis' names like as Shahab al Din Suhrawardi, Jami, Molana, Maulana Rumi, Ibn 'Arabi and many others entered the analytic language of Persian Miniature Arts. There are many publications and research works in the past decades that explained the relation between artists and Sufis but until now no one able to propose an aesthetical term and language for Persian miniature works. Beside historical, literal and formal analysis; researchers required to establish an acceptable and accurate terms which proved the connections between miniature works and mystical concepts. To find the missing linkage, this research tried to.start with explanation of historical backgrounds, misunderstanding of Western scholars and definition of Alam al-Mithal as the main concept in Sufi practice and then use a methodology based on the contextual field of paintings which is Iran. Formal analysis of miniature works contained the major visual concepts like as Light, Time, Space, Color, Geometrical Composition and the paintings were selected from all four famous Persian Miniature Schools. At the same time in the next chapter this research tried to explain the visual terms of Alam al-Mithal to find out the similarity between visual terms of Persian Miniature Paintings and Alam al-Mithal.